Investigating the Relationship between Nurses’ Health Informatics Competencies, Participation in Administrative Decision-Making, and Quality of Patient Care in Hafr Al-Batin: A Cross-Sectional Survey Study - Mohammad Wafi Aamen Alharbi; Suliman Mohatlef Alshammari; Mohammed Esmail Yahya Adawi Hashdi; Abdulsalam Hmooud Ammash Alshammari; Abdulrahman Saif Abdullah Alsahli; Ali Kulaib Saleh Aljohani (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The integration of health informatics in nursing practice has become increasingly important in enhancing the quality of patient care. This study aimed to investigate the relationship between nurses’ health informatics competencies, their participation in administrative decision-making, and the quality of patient care in Hafr Al-Batin, Saudi Arabia. Methods: A cross-sectional survey study was conducted among 250 nurses working in various healthcare facilities in Hafr Al-Batin. The survey questionnaire assessed nurses’ health informatics competencies, participation in administrative decision-making, and perceived quality of patient care. Descriptive statistics, Pearson’s correlation, and multiple linear regression analysis were used to analyze the data. Results:The majority of nurses demonstrated moderate to high levels of health informatics competencies. Nurses’ participation in administrative decision-making was found to be significantly associated with their health informatics competencies (r=0.68, p<0.001). Additionally, both health informatics competencies (β=0.42, p<0.001) and participation in administrative decision-making (β=0.35, p<0.001) were significant predictors of the quality of patient care. Conclusion: The findings highlight the importance of enhancing nurses’ health informatics competencies and promoting their participation in administrative decision-making to improve the quality of patient care in Hafr Al-Batin. Healthcare organizations should invest in training programs and create supportive environments that foster nurses’ involvement in decision-making processes.